What is the American model really about? Soft budgets and the Keynesian devolution - James K. Galbraith (Levy Economics Institute of Bard College, 2003)
The American Model serves as a point of reference in discussions of economic policy around the world, especially in Europe. Many claim that the American version of the free market represents an ideal type - it is the highest form of capitalism. Senior Scholar James K. Galbraith argues, however, that the United States has relied heavily on government intervention in housing, health care, pensions, and education. Not only have these programs been largely successful and popular, but they also provide a Keynesian stimulus to spending that helps account for the strength of the US economy. Now that the United States is in a weak, jobless recovery, the key to restoring growth may lie in the kinds of governmental programs that have helped to sustain and stabilize the US economy in the past.
Keywords: 330; Vollbeschäftigung; Öffentliche Sozialausgaben; Budgetrestriktion; Wirtschaftspolitik; Finanzpolitik; USA